Scholar’s Viewpoints about Periadriatic Basin (onshore Albania) - Aliaj, Shyqyri; Mesonjesi, Agim (European Journal of Applied Sciences, 2023)
The Albanian and foreign scholar’s viewpoints about the structure formation of the Periadriatic Foredeep Basin are summarized based on the data taken from the following two investigated field studies: a) the geological & geophysical studies and b) the seismotectonic studies for the November 26, 2019, Mw 6.4 Durres earthquake. Based on the investigated geological and geophysical studies for the formation of the Periadriatic Basin Structure the two different scholar’s opinions are examined, as follows: (i) The first scholar’s group formed by Papa (1971), Velaj et al. (1999), Skrami & Aliaj (1995), Skrami (2001), Melo (2002), Aliaj et al. (1995, 2018), Aliaj (1998, 2000, 2004, 2006, 2012, 2021) and Bega (1995) explained the formation of the Periadriatic Basin structure through a rearranged (superimposed) development, and (ii) the second scholar’s group formed by Roure et al. (2004), Scrocca et al. (2008), Bega and Schleder (2017) and Bega (2020) explained the Periadriatic Basin formation through an inherited development. Xhafa et al. (2002) and Xhomo et al. (2002, 2005) explained the formation of the central part of the Periadriatic Basin through inherited development, while its marginal parts through the rearranged development. The Periadriatic Foredeep Basin is a Pull-apart Basin installed in the Middle Miocene (Serravallian) between the South Adriatic Basin and Tirana marginal basin, where it takes a graben shape delimited by the Durresi-Frakulla and PrezaRova-Bishqemi normal faults. The investigated seismotectonic studies for 26 November 2019, M6.4 Durres earthquake reveal the architecture of the Adria-Albanides collision that played the main role in the structural rearrangement of the Periadriatic Basin due to the pre-Serravallian or ends Langhian, intra-Messinian, Miocene-Pliocene boundary and early Pleistocene compressional tectonic phases. Deformation of orogenic crust at the Albanides-Adria collision zone during Tertiary occurred and occurs into both levels: i) a basal fold-and-thrust system in the Ionian Zone, that accommodated an increasing amount of SW directed shortening, and ii) a structurally higher system of thrust faulting affecting the overlying structure of the Periadriatic Depression, that underwent a strong structural rearrangement.